Bibliometric Analysis of Development Map and Research Direction of Development of Study Quran on Scopus Database - Mahmudi, Mahfud; Nirwana AN, Andri (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
We conducted this study with the aim of mapping the development and direction of Development of Study Quran research in scopus indexed publications. We used bibliometric analysis techniques in this study to explore all publications indexed in the scopus database on the Development of Study Quran from 1981 to 2023. The data obtained was analyzed using excel and rr studio. We used Vos viewer to perform a visual analysis of the simultaneous occurrence of keywords and documents. The author found 295 publications that matched the function, subject and criteria set. The results of this study show an annual growth rate of 8.44%. With the most publications on Development of Study Quran in 2020. Malaysia is the country that contributes the most publications with a total of 20 affiliates from Universiti Kebangsaan Malaysia. Choudhury, Diyana, Hanafi, Ikhsan, Kadir, Murtadho, and Noor are the most productive authors in the theme of Development of Study Quran. Bibliometric analysis conducted on scopus data. This research does not account for other national and international datasets. In addition to offering suggestions for further research, this study offers a concise summary of the literature available to scholars engaged in the creation of study quran.